(untitled) (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Premessa - 2. La giurisprudenza della Suprema Corte - 3. L’introduzione del § 1631, lett. d, nel BGB tedesco e la giurisprudenza di Colonia - 4. Risoluzioni e raccomandazioni del Consiglio d’Europa - 5. Il recente dibattito islandese - 6. Prospettive per l’Italia: necessità o ultroneità di una legge ad hoc? - 7. Osservazioni conclusive. Notes on ritual circumcision in Ecclesiastical and Religious Law. ABSTRACT: This paper deals with the delicate issue of ritual circumcision in Ecclesiastical and Religious Law. After having investigated the etymological origin of the word and reconstructed the history of the practice in question – distinguishing between circumcisions: a) therapeutic or prophylactic, b) ritual, c) cultural or ethnic – the focus is on the jurisprudential orientations of the Italian Court of Cassation. The solution proposed by the judgment of 24 November 2011, n. 43646, is carefully read and compared with the EU’s law, the German legislation and the results of the recent Icelandic debate. Nevertheless, the absence of an ad hoc law on circumcision does not represent a vulnus in the Italian legal system, since the discipline can be found in the positive law in force, and even before in constitutional principles, as interpreted by the jurisprudence of merit and legitimacy. On the contrary, the essay raises the question that the introduction of a law on circumcision would not only be superfluous (for ethical and cultural reasons, even before legal ones), but also late".